2007
DOI: 10.1001/archpsyc.64.5.577
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events and Posttraumatic Stress in Childhood

Abstract: In the general population of children, potentially traumatic events are fairly common and do not often result in PTS symptoms, except after multiple traumas or a history of anxiety. The prognosis after the first lifetime trauma exposure was generally favorable. Apart from PTSD, traumatic events are related to many forms of psychopathology, with the strongest links being with anxiety and depressive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
807
9
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,235 publications
(896 citation statements)
references
References 47 publications
44
807
9
18
Order By: Relevance
“…In this study, the observed independent association between exposure to a single injury and the subsequent increased risk of receiving psychiatric diagnoses is particularly relevant given that the vast majority of injuries were relatively minor (MAXAIS of 1 or 2). In contrast to prior reports, this investigation did not find a significantly elevated risk of disruptive behavior disorder diagnoses for youths exposed to traumatic injury after analyses adjusted for demographic and preinjury clinical characteristics (1,30). …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, the observed independent association between exposure to a single injury and the subsequent increased risk of receiving psychiatric diagnoses is particularly relevant given that the vast majority of injuries were relatively minor (MAXAIS of 1 or 2). In contrast to prior reports, this investigation did not find a significantly elevated risk of disruptive behavior disorder diagnoses for youths exposed to traumatic injury after analyses adjusted for demographic and preinjury clinical characteristics (1,30). …”
Section: Discussioncontrasting
confidence: 99%
“…Also of note, traumatic injuries incurred before 2001 were independently associated with an increased risk of postinjury psychiatric diagnoses and psychotropic medication prescription. Prior reports suggest that pre-event psychopathology and recurrent trauma among youths and their family members are associated with an increased risk of developing PTSD and related psychiatric disorders (1,21,22,30,55). These collective findings suggest that postinjury screening and intervention protocols in acute care and pediatric practice settings may need to target high-risk children and adolescents who have been exposed to multiple injury events or who have a history of psychiatric disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trauma exposure in childhood and adolescence is common (Copeland, Keeler, Angold, & Costello, 2007), with a substantial minority of trauma‐exposed youth going on to develop PTSD (Alisic et al., 2014). PTSD may be chronic in youth, potentially lasting years (Morgan, Scourfield, Williams, Jasper, & Lewis, 2003; Yule et al., 2000).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is characterized by disabling symptoms from four clusters; reexperiencing (e.g., flashbacks and nightmares about the trauma; avoidance (e.g., efforts to not think about or talk about the trauma); negative cognitions and mood (e.g., a persistent and distorted sense of blame of self or others to an inability to remember key aspects of the event); and hyperarousal (e.g., anger outbursts and hypervigilance for threat; Diagnostic and Statistical Manual of Mental Disorders 5th edition [DSM‐5]; American Psychiatric Association [APA], 2013). Traumatic events with the potential to lead to PTSD are experienced by up to two thirds of children by 16 years of age (Copeland, Keeler, Angold, & Costello, 2007), including in preschool and early school years, even when excluding abuse. However, the DSM‐5 was the first edition to include tailored criteria capturing the differential presentation of the disorder in very young children younger than 6 years old.…”
mentioning
confidence: 99%